Features of compensation of harm, caused to life and health of the tourist, according to the legislation of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
This article discusses the features of compensation of harm, caused to life and health of the tourist, according to the legislation of the Republic of Kazakhstan. The correlation of norms of the legislation on tourist activity with the General provisions on compensation of harm of life and health is shown. Attention is paid to the incorporation of norms on liability for harm to life and health in the contract on rendering of tourist services. Examples from the practice on compensation of harm for life and health of tourists are analyzed. Key categories in these relations are identified.Key words: life, health, liability, tourist, compensation of harm.